Campus policing : an ethnography of the University of Cape Town Campus Control Unit - Ncube, Lashias (1996)
Includes bibliography.The aim of undertaking the project was to investigate the activities of the University of Cape Town Campus Control unit. The study is based on the premise that there is an underestimation of Campus Control work. A number of basic questions were examined in the field. The researcher sought to determine, among other things, the extent to which the unit's work is invisible, and the extent to which the university community's reported ambivalence and indifference to Campus Control practice a result of a lack of clarity regarding the role of the unit within the university. The research also moved from the premise that there is too great an emphasis on the use of crime statistics as indices of the unit' effectiveness. The racial and gender configuration of assignments was also investigated as was the training offered to new and old recruits. Participant observation as a body of different methods and techniques of research was used. The researcher spent six weeks in the field with the campus control officers in order to experience the demands of policing from "the native's point of view". The unit is in the process of transforming. It seeks to embrace the discourse of community participation with a view to getting the entire community involved in the provision of its own safety and security. The community involvement initiatives are also designed to improve the relationship between the unit and the community. In the past, the relationship has been a very traumatic one, fraught with mistrust and had far-reaching consequences for the unit's performance. The study comes to the conclusion that both women and blacks in Campus Control are a case of structural marginality. The unit does not reflect the racial and gender composition of the community it serves. It was also discovered that some of the unit's glaring shortcomings are played out in the sphere of training. The study should help members of the university community to understand and appreciate the role of this indispensable unit within the university community